Optimization and test of the heating parts of gas-fired tea fixation and shaping machine - Qilong Wu; Qilong Wu; Lei Yu; Chengmao Cao; Chengmao Cao; Kuan Qin; Kuan Qin; Yi Jing; Yuhao Dai; Yuhao Dai; Xinliang Guo; Xinliang Guo; et al. (Frontiers in Sustainable Food Systems)
IntroductionThe uneven heating of the U-shaped multi-groove pot in gas-fired tea fixation and shaping machines results in inconsistent quality of tea leaves.MethodsA three-dimensional model of the gas-fired tea fixation and shaping machine was established by using SOLIDWORKS software. With the use of ANSYS finite element software, the orthogonal experiment method was applied to analyze and optimize the design of the spacing arrangement, the shape of the heating parts, and the heat conduction temperature field.ResultsResults show that the optimized heating parts significantly reduce the temperature difference on the surface of the U-shaped multi-groove pot, and the surface temperature field of the multi-groove pot is more uniform, which greatly improves the efficiency and quality of fresh tea leaf fixation and shaping. Prototype temperature and tea sample fixation ratio tests verified that the optimized heating components significantly improved the temperature uniformity of the U-shaped multi-groove pot and the quality of the finished tea.DiscussionThe research findings provide insights for further improving the uniformity of the U-shaped multi-groove pot’s temperature in the tea fixation and shaping machine.